Amide Synthesis by Transamidation of Primary Carboxamides - Kolympadi Marković, Maria; Marković, Dean; Laclef, Sylvain (Synthesis, 2020)
The amide functionality is one of the most important and widely used groups in nature and in medicinal and industrial chemistry. Because of its importance and as the actual synthetic methods suffer from major drawbacks, such as the use of a stoichiometric amount of an activating agent, epimerization and low atom economy, the development of new and efficient amide bond forming reactions is needed. A number of greener and more effective strategies have been studied and developed. The transamidation of primary amides is particularly attractive in terms of atom economy and as ammonia is the single byproduct. This review summarizes the advancements in metal-catalyzed and organocatalyzed transamidation methods. Lewis and Brønsted acid transamidation catalysts are reviewed as a separate group. The activation of primary amides by promoter, as well as catalyst- and promoter-free protocols, are also described. The proposed mechanisms and key intermediates of the depicted transamidation reactions are shown.1 Introduction2 Metal-Catalyzed Transamidations3 Organocatalyzed Transamidations4 Lewis and Brønsted Acid Catalysis5 Promoted Transamidation of Primary Amides6 Catalyst- and Promoter-Free Protocols7 Conclusion
Keywords: primary amides; transamidation; amide bond; carboxamides; amine formylation